1989
DOI: 10.1002/ijc.2910430206
|View full text |Cite
|
Sign up to set email alerts
|

Abrogated NK‐cell lysis of human papillomavirus (HPV)‐16‐bearing keratinocytes in patients with pre‐cancerous and cancerous HPV‐induced anogenital lesions

Abstract: Natural-cell-mediated cytotoxicity against K-562 erythroleukemic cells and human papillomavirus (HPV)-16 harboring Sk-v keratinocytes was tested in 38 age- and sex-matched healthy volunteers and in patients with HPV-induced benign and malignant anogenital lesions: 9 persons with HPV-16-induced bowenoid papulosis (BP), 8 with anogenital carcinomas (5 with HPV-16- or 33-associated squamous-cell carcinomas of Bowen's type and 3 with HPV-6-associated Buschke-Loewenstein verrucous carcinomas) and 12 with HPV-6-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Our experiments show that neither synthesis nor transport to the cell surface of HLA-C/E is affected by E5 expression, leading to the conclusion that E5 selectively inhibits surface expression of HLA-A and HLA-B. NK cells of patients with HPV-induced anogenital lesions are incapable of specific killing HPV-16-infected cells, 46 although the mechanism by which this occurs is as yet unknown. Moreover, concordant with loss of MHC class I molecules that present viral peptides, there is a very low frequency of HPV-specific HLA-A-restricted CTLs in patients infected with HPV-16, an order of magnitude lower than those found in other viral infections, including influenza A and EBV.…”
Section: Discussionmentioning
confidence: 59%
“…Our experiments show that neither synthesis nor transport to the cell surface of HLA-C/E is affected by E5 expression, leading to the conclusion that E5 selectively inhibits surface expression of HLA-A and HLA-B. NK cells of patients with HPV-induced anogenital lesions are incapable of specific killing HPV-16-infected cells, 46 although the mechanism by which this occurs is as yet unknown. Moreover, concordant with loss of MHC class I molecules that present viral peptides, there is a very low frequency of HPV-specific HLA-A-restricted CTLs in patients infected with HPV-16, an order of magnitude lower than those found in other viral infections, including influenza A and EBV.…”
Section: Discussionmentioning
confidence: 59%
“…Decreased NK cell lysis of HPV-16 ϩ keratinocytes in subjects with SIL or carcinomas has been reported (82). The same group has shown that decreased recognition of HPV-16 ϩ keratinocytes is re-lated to unresponsiveness of PBMC to immunostimulatory cytokines such as IL-2 and IFN-␣ (86).…”
Section: School Of Medicine University Of California San Francisco mentioning
confidence: 95%
“…Using HLA-2.1 transgenic mice four immunogenic peptides were identified in vivo [E6 (29)(30)(31)(32)(33)(34)(35)(36)(37)(38), E7 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), E7 (82)(83)(84)(85)(86)(87)(88)(89)(90), and E7 (86-93)]. In addition, CTL induction of PBMC from humans confirmed immunogenicity, in vitro, of three of the four peptides [E7 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), E7 (82)(83)(84)(85)(86)(87)(88)(89)(90), and E7 (86-93)]. CTL to one of the...…”
Section: Adaptive Cell-mediated Immunitymentioning
confidence: 99%
“…NK cell assay. NK cell activity of preincubated PBL was tested against human K562 myelogenous leukemia target cells in a 4-hour "Cr-release assay, as described elsewhere (22). Briefly, PBL and lo4 K562 cells were mixed in wells of round-bottom multiwell plates at effector-to-target cell ratios ranging from 80: 1 to 10: 1.…”
Section: Methodsmentioning
confidence: 99%